Performance Appraisal & Promotion Practices on Private Commercial Bank in Bangladesh: A Case Study from Pubali Bank Ltd. - Hossain, Maksuda; Abdullah, Abu Md.; Farhana, Shila (Asian Business Review, 2012)
This paper has been prepared on performance appraisal & promotion practice of Pubali Bank Ltd. Performance appraisal being a critical part of human resource management carries huge significance to run an organization smoothly. As the name implies management does not have to face obstacles regarding employees if such appraisal is done appropriately with proper implication on promotion. This process of performance appraisal has been presented here the way it is followed by Pubali Bank Ltd. The objective of the paper has also been to present the performance appraisal of employees of this bank. After discussion there is findings section which shows various appraisal problems approaching by the employees and organization as well. To avoid any sudden setback in future, well defined steps have been recommended at the end of this paper.